Association of systemic health and functional outcomes with changes in hard exudates associated with clinically significant macular oedema over the natural course of the disease. Issue 6 (27th May 2010) - Kameda, Yusuke; Kumakawa, Makiko; Endo, Naoko; Iwamoto, Yasuhiko; Kitano, Shigehiko
Abstract : Aim: Hard exudates associated with clinically significant macular oedema (CSMO) do not always increase without laser photocoagulation and can generally be classified as regressing or progressing. We studied the systemic differences and functional outcomes between the two groups. Methods: In this retrospective observational controlled study, we compared blood pressure, biochemical parameters and best corrected visual acuity (BCVA) between 26 patients with regressed hard exudates with CSMO (group A) and 27 patients with progressing hard exudates with CSMO (group B). The eyes had no history of ophthalmic treatments including laser therapy for diabetic retinopathy or maculopathy until the end of the study. Results: Group B had significant increases in the mean total cholesterol (TC) (p=0.0194) and mean low-density lipoprotein (LDL) cholesterol (p=0.0147) after at least 6 months of follow-up compared with group A. The final mean BCVA was significantly (p=0.0189) higher in group A than group B. A separate within-group analysis showed a significant (p=0.0015) decrease in BCVA from baseline in group B at the final visit. Conclusion: For hard exudates associated with CSMO, strict lipid-lowering therapy, especially regulation of elevated TC and LDL, before a decrease in visual acuity might result in better macular anatomical outcomes and visual preservation through the natural course of the disease.